1999
DOI: 10.1016/s0009-9236(99)70071-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic polymorphisms of the β -adrenergic receptor on albuterol bronchodilator pharmacodynamics

Abstract: The beta2-adrenergic receptor gene polymorphism is a major determinant of bronchodilator response to albuterol. Future pharmacodynamic studies of beta2-agonists should include determination of 02-adrenergic receptor genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
136
2
9

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(165 citation statements)
references
References 20 publications
18
136
2
9
Order By: Relevance
“…However, more recent in vivo work in humans has shown the Arg16Gln27 haplotype is the form of the receptor that is associated with agonist-promoted desensitization (Dishy et al 2001). Genetic studies of these polymorphisms have found them to be associated with asthma severity Weir et al 1998), bronchial hyperreactivity (BHR) Ramsay et al 1999), bronchodilator (BD) response (D'Amato et al 1998;Lima et al 1999;Martinez et al 1997;Ulbrecht et al 2000) and lung function (Summerhill et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent in vivo work in humans has shown the Arg16Gln27 haplotype is the form of the receptor that is associated with agonist-promoted desensitization (Dishy et al 2001). Genetic studies of these polymorphisms have found them to be associated with asthma severity Weir et al 1998), bronchial hyperreactivity (BHR) Ramsay et al 1999), bronchodilator (BD) response (D'Amato et al 1998;Lima et al 1999;Martinez et al 1997;Ulbrecht et al 2000) and lung function (Summerhill et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…56 Several other smaller studies have observed similar effects of Arg 16 Gly genotypes on response to acute SABA therapy with the notable exception of a study by Taylor and co-workers. 47,[58][59][60][61][62][63] Taylor and co-workers selected 176 patients based solely on a physician's diagnosis of asthma and found no relationship between Gly 16 Arg genotypes or ADRβ2 haplotypes and responsiveness to a single dose of albuterol. 60 In the Genetics of Asthma in Latino Americans (GALA) study, Choudhry et al investigated the pharmacogenetic relationship of Gly 16 Arg genotypes with albuterol-induced FEV1 reversibility in two ethnic groups (365 Puerto Rican asthmatics and 294 Mexican-Americans) through family-based and cross-sectional analyses.…”
Section: Adrβ2 Pharmacogenetics Asthma Susceptibility and Responsivmentioning
confidence: 99%
“…For instance, the Gly16 variant is associated with more severe asthma 31 and decreased response to an ␤ 2 -AR agonist. 32 Conflicting data exist on the effect of ␤ 2 -AR polymorphisms on blood pressure in the general population. 28,30,33 Nevertheless, healthy whites with Gly16 and Glu27 variants present higher blood pressure.…”
Section: Association Of ␤ 2 -Ar Polymorphisms With Potsmentioning
confidence: 99%